1983
DOI: 10.1093/ptj/63.11.1776
|View full text |Cite
|
Sign up to set email alerts
|

Objective Assessment with Establishment of Normal Values for Lumbar Spinal Range of Motion

Abstract: The purpose of this article is to present an assessment method, in conjunction with age-related normal values, for lumbar spinal range of motion. Lumbar flexion, lumbar extension, and right and left lateral flexion were measured on 172 subjects by a combination of goniometry and spinal distraction techniques. Normal values are given for six age groups; each group had a range of 10 years. The results demonstrate that a significant decrease in lumbar spinal range of motion is expected with increasing age. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 10 publications
6
80
3
Order By: Relevance
“…Several studies report varying reliability from low [4,21,32,41] to high [14,20,28,31,44]. Within our study, we did not find any statistically significant correlation between the modified Schober test and MRI findings.…”
Section: Mobility Testscontrasting
confidence: 58%
See 1 more Smart Citation
“…Several studies report varying reliability from low [4,21,32,41] to high [14,20,28,31,44]. Within our study, we did not find any statistically significant correlation between the modified Schober test and MRI findings.…”
Section: Mobility Testscontrasting
confidence: 58%
“…Some studies found gender, age, height, obesity and sitting-to-standing ratio to affect ROM [1,3,10,14,29,35], while others could not find any correlation between [11,24,29,30]. ROM is not only affected by anthropometric data but also affected by factors such as pain [11,29,30], motivation [7], time of day [11] and sport [5].…”
Section: Discussionmentioning
confidence: 99%
“…While age and to a lesser degree gender have been shown to play a role on lumbar RoM [11], a larger age effect in men, as observed previously [21] is not visible in the current study. The functional tests (fingertip-to-floor distance, Schober and Ott signs), which are considered to be reliable and objective [23], also show a dependency on age, but not as clearly as the results obtained using Epionics SPINE. Here, the high correlations for the three measurements showed good reliability of Epionics SPINE.…”
Section: Discussionmentioning
confidence: 91%
“…More clinically friendly, inexpensive techniques include goniometers [16,[18][19][20][21], inclinometers [17,[22][23][24][25][26][27] and flexicurves [28][29][30][31]. Goniometers and inclinometers are secured or held directly over previously palpated vertebrae, producing a measure that is limited to a single thoracic, lumbar, or sacral region of the spine [16,17,19,22,25].…”
Section: Introductionmentioning
confidence: 99%